Distributed Leadership and the Visibility/Invisibility Paradox in On-Line Communities - Jameson, Jill (Human Technology, 2011)
This paper analyzes the role of distributed leadership in three on-line communities, reflecting on an observed visibility/invisibility paradox in leadership within these communities. Leaders who downplay their seniority and assume a degree of invisibility, allocating discretionary powers to subordinate levels in an organizational hierarchy, may facilitate the emergence of distributed leadership. Yet, simultaneously, leader-led relations are enabled by high leadership visibility. This paradox—that leaders need to be both highly visible and also invisible, or hands-off, when the occasion requires it—was derived from prior research into e-learning communities and tested in the analysis of discussions from on-line communities using a case study pattern-matching process. The operation of both visibility and invisibility in leadership is a key issue for enabling effective collaborations in distributed leadership situations based on trust. Such collaboration fosters positive group interaction and participative decision making in a consensus facilitated through leadership distribution amongst on-line community members.